Lifestyle intervention strategies in early life to improve pregnancy outcomes and long-term health of offspring: a narrative review. (9th November 2018) - Gaillard, Romy; Wright, John; Jaddoe, Vincent W.V.
Abstract: Adverse exposures during fetal life and the postnatal period influence physical, cognitive and emotional development, and predispose to an increased risk of various chronic diseases throughout the life course. Findings from large observational studies in various populations and experimental animal studies have identified different modifiable risk factors in early life. Adverse maternal lifestyle factors, including overweight, unhealthy diet, sedentary behavior, smoking, alcohol consumption and stress in the preconception period and during pregnancy, are the most common modifiable risk factors leading to a suboptimal in-utero environment for fetal development. In the postnatal period, breastfeeding, infant growth and infant dietary intake are important modifiable factors influencing long-term offspring health outcomes. Despite the large amount of findings from observational studies, translation to lifestyle interventions seems to be challenging. Currently, randomized controlled trials focused on the influence of lifestyle interventions in these critical periods on short-term and long-term maternal and offspring health outcomes are scarce, have major limitations and do not show strong effects on maternal and offspring outcomes. New and innovative approaches are needed to move from describing these causes of ill-health to start tackling them using intervention approaches. Future randomized controlled lifestyle intervention studies and innovative observational studies, using quasi-experimental designs, are needed focused on the effects of an integrated lifestyle advice from preconception onwards on pregnancy outcomes and long-term health outcomes in offspring on a population level.